The first in-depth photometric study of the four δ Scuti stars using TESS data - Poro, A.; Azarara, H.; Sarostad, A.; Poor, N. K.; Aliakbari, R.; Nasirian, S.; Momeni, S.
The first in-depth photometric study of four δ Scuti stars was performed. We used time series data from the Transiting Exoplanet Survey Satellite (TESS) that is available in different sectors. According to the extracted maxima from TESS space-based observations, we calculated an ephemeris for each star. We estimated the physical parameters of the target stars based on the Gaia Data Release 3 (DR3) parallax method. The results obtained for the surface gravity of the stars are consistent with the reports of the TESS Input Catalog and Gaia DR3. We estimated the pulsating constant based on the physical parameters and period of the stars. Therefore, we found that the stars 2MASS 15515693-7759002 and 2MASS 07513202+0526526 belong to the fundamental, while 2MASS 00044615+4936439 and 2MASS 10215638-3326137 relate to the first overtone. The Fourier analysis using the Period04 program was done for each star. As we showed in the Hertzsprung-Russell (H-R) diagram, the stars are located in the instability strip of the δ Scuti stars region. Four target stars were found to be of the low-amplitude  Scuti star type.
Keywords: Astrophysics